Acute and late side effects to salivary glands and oral mucosa after head and neck radiotherapy in children and adolescents. Results of the "Registry for the evaluation of side effects after radiotherapy in childhood and adolescence". Issue 8 (11th July 2014) - Bölling, Tobias; Weege, Julia; Eich, Hans Theodor; Timmermann, Beate; Meyer, Frank‐Michal; Rübe, Christian; Kortmann, Rolf‐Dieter; Fischedick, Karin; Rödel, Claus; Koch, Raphael; Willich, Normann
Abstract Background The registry for the evaluation of side effects after radiotherapy in childhood and adolescence (RiSK) was established to prospectively characterize radiation‐associated side effects. The purpose of this analysis was to characterize side effects after radiotherapy to the head and neck in children and adolescents. Methods Radiation doses have been collected across Germany since 2001. Acute and late side effects were characterized. Results Until January 2010, 133 patients (median age, 12.7 years) were recruited who had received radiotherapy to the salivary glands. Toxicity evaluation was available for 114 patients (median follow‐up, 2.9 years). Acute and late toxicity significantly depended on the maximum radiation dose to the salivary glands. An increase of the mean value of maximum dose of 1 Gray (Gy) to the submandibular glands resulted in an odds ratio of 1.04 (range, 1.00–1.08; p = .039) for acute toxicities of the salivary glands and 1.08 (range, 1.03–1.13; p = .001) for acute mucosal toxicities. Conclusion These data can be used for an individual risk assessment in pediatric head and neck radiotherapy. © 2014 Wiley Periodicals, Inc. Head Neck37: 1137–1141, 2015